Hubungan Penguasaan Kosakata dengan Kemampuan Membaca Pemahaman Peserta Didik Kelas III SD - Riri Rahmadhani Tanjung; Elfia Sukma; Yalvema Miaz (e-Journal Inovasi Pembelajaran Sekolah Dasar, 2018)
This article was written to describe the relationship between vocabulary mastery and student’s reading comprehension. This research type is correlation research by using quantitative approach. there are two data to be processed. First, vocabulary mastery. Second, reading comprehension. The design used in this study is the design korelasinal with a population of all students class III which amounted to 162 people. Sampling method used is Cluster Random Sampling which amounted to 52 people. to test the hypothesis of this study using t test statistic with 5% level of significance (0.05). The result of this research is first, the mastery of vocabulary of learners is in sufficient qualification (66,63). Second, students' reading comprehension ability is in good qualification (75,57). Third, there is a significant relationship between vocabulary mastery and reading comprehension ability on n-2 degrees of freedom and significance level of 0.05 research results prove that tcount is bigger than ttable that is 11,090> 2,009.Keywords: Relationship vocabulary, reading comprehension, student